ROLE OF NEURONAL NO-SYNTHASE GENE POLYMORPHISM IN FORMATION OF ATOPIC DERMATITIS IN CHILDREN AND IN SENSITIVITY TO THERAPY - I.Yu. Smirnova (Union of pediatricians of Russia, 2009)
It's known, nitrogen oxide takes part in formation of the allergic inflammation. One of the enzymes, which produce NO, is the neuronal NO synthase (n NOS). The research objective is to determine the value of n NOS 276С-Т gene polymorphism in formation of atopic dermatitis in children. The research incorporated 119 children aged from 1 to 18, suffering from atopic dermatitis. The author has identified that n NOS 276С-Т gene polymorphism is associated with the development of atopic dermatitis in children, as well as with the best response to the performed basic therapy. The research proved that there is no relation between n NOS 276С_Т gene polymorphism and illness severity, level of IgE in blood serum.Key words: atopic dermatitis, children, basic therapy, neuronal NO synthase, gene polymorphism.